Role of institutions and institutional constraints in watershed programmes : a case study of Karkara watershed, Hazaribagh, Jharkand - G.P. Reddy,; R.C. Srivastava,; H.N. Verma, (Journal of Agricultural Extension Management, 2025)
A watershed programme is a multi-disciplinary programme. Such programmes requires an integrated approach because they include components that are the responsibility of several agencies. Problems of land mismanagement occur on upland areas because of the inappropriate use of farming technology. Cultivation of steep slopes should be tolerated to some extent because of over population, but appropriate technology should be introduced to poor farmers who live in the remote areas of upland watershed. Bench technology and alley cropping, for example, can be introduced in a practical way on model farms which will encourage their adoption by upland farmers in expansion areas